'Candidatus Oscillochloris fontis': a novel mesophilic phototrophic Chloroflexota bacterium belonging to the ubiquitous Oscillochloris genus. Issue 8 (4th May 2019) - Gaisin, Vasil A; Burganskaya, Ekaterina I; Grouzdev, Denis S; Osipova, Natalya S; Ashikhmin, Aleksandr A; Sinetova, Maria A; Krutkina, Maria S; Bryantseva, Irina A; Sukhacheva, Marina V; Kochetkova, Tatiana V; Koziaeva, Veronika V; Kalashnikov, Aleksandr M; et al.
ABSTRACT: We present the results of a study of mesophilic anoxygenic phototrophic Chloroflexota bacteria from Mechigmen hot spring (the Chukotka Peninsula) and Siberia. According to 16S rRNA phylogenetic analysis, these bacteria belong to Oscillochloris trichoides . However, sequencing the draft genome of the bacterium from the Chukotka and analysis of the average nucleotide identity, as well as in silico DNA-DNA hybridization, reveal that this bacterium belongs to a novel species within the Oscillochloris genus. We, therefore, propose ' Candidatus Oscillochloris fontis' as a novel taxon to represent this mesophilic alkaliphilic anaerobic anoxygenic phototrophic bacterium. Spectrophotometry and high-performance liquid chromatography analysis show that the bacterium possesses bacteriochlorophylls c and a, as well as lycopene, β-carotene and γ-carotene. In addition, transmission electron microscopy shows the presence of chlorosomes, polyhydroxyalkanoate- and polyphosphate-like granules. The genome of ' Ca . Oscillochloris fontis' and the Siberian strains of Oscillochloris sp. possess the key genes for nitrogenase complex ( nif H) and ribulose-1, 5-bisphosphate carboxylase/oxygenase ( cbb L), as previously described for O. trichoides DG-6. The results presented here, and previously published data, show that Oscillochloris bacteria from different aquatic environments have the potential for CO2 and N2 fixation. Additionally, we describe a new primer system for the detection of RuBisCo form I. Abstract : We present the results of a study on phylogenetic and functional diversity of Oscillochloris bacteria and description of 'Candidatus Oscillochloris fontis' bacterium from the Chukotka Peninsula.